Effect of Current Ratio and Debt to Equity Ratio on Return on Assets at PT Pertamina (Persero) Marketing Operational Region I - Januri Januri (International Journal Reglement & Society (IJRS), 2021)
The purpose of this study was to analyze and determine the effect of Current Ratio on Return On Assets significantly on PT. Pertamina (Persero) Operational Marketing Region 1 Period 2015-2019. To analyze and find out the effect of Debt to Equity Ratio on Return On Assets significantly on PT. Pertamina (Persero) Operational Marketing Region 1 Period 2015-2019. To analyze and know the effect of Current Ratio and Debt to Equity Ratio significantly on PT. Pertamina (Persero) Operational Marketing Region 1 Period 2015-2019. Based on the research conducted on PT. Pertamina (Persero) MOR 1 Period 2015-2019 priode 2015 to 2019, it can be concluded that there is an influence between the Current Ratio (CR) on Return On Assets (ROA). Based on the research conducted on PT. Pertamina (Persero) MOR 1 Period 2015-2019, it can be concluded that there is an influence between Debt to Equity Ratio (DER) on Return On Assets (ROA). Based on the research conducted on PT. Pertamina (Persero) MOR 1 Period 2015-2019 priode 2015 to 2019, it can be concluded that there is simultaneous influence between Current Ratio (CR), and Debt to Equity Ratio (DER) on Return On Assets (ROA). R-Square value above is 68.6 % this means that 68.6% variation in Return On Assets value is determined by the role of the variation of Current Ratio and Debt to Equity Ratio. In other words, the contribution of Current Ratio and Debt to Equity Ratio in influencing Return On Assets is 68.6% while the remaining 31.4% is influenced by other variables not included in this study such as asset structure and sales growth